Assessment of Heavy Metal Contamination and Removal Using ceratophyllum Demersum L.: a Case Study - Gören, Ayşegül Yağmur; Karaoglu, Aybike Gul; Gören, Ayşegül Yağmur; Kobya, Mehmet; Goren, Aysegul Yagmur; Mese, Esra; Tepe, Melike (inderscience Enterprises Ltd, 2024)
Assessment of heavy metal contamination in aquatic ecosystems continues to remain challenging. In this regard, Ceratophyllum demersum L. (C. demersum L.) is a common species found in rivers and can be used as a bioindicator to see the accumulation of heavy metals in the plant body. In this study, we aimed to investigate the accumulation of toxic metals and their effects on photosynthetic pigment content in plants for different seasons. The highest metal accumulations were observed in October 2019. The mean boron concentrations were 399 mg/kg in October 2019, while they were measured as 163 mg/kg in July 2020, most probably due to the decreasing agricultural activities in the studied area. However, the highest metal concentrations (aluminium 3,941 mg/kg and iron 5,161 mg/kg) were measured in July 2010. Moreover, the pigment content values were decreased with the increasing metal concentration in plants. The highest pigment content of 4.7 mu g/g was observed in October 2019, related to the low metal contamination in this season. Overall, C. demersum L. is a promising bioindicator of heavy metal pollution in water bodies with a significant amount of heavy metal accumulation capacity in a sustainable manner.
Keywords: Ceratophyllum demersum L; heavy metals; abiotic stresses; phytoremediation